EVALUASI PERSPEKTIF POLITIK TRUMP PADA "SAVE AMERICA RALLY" - Wijaya, Ikha Adhi; Annas, Annas; Sumarlam, Sumarlam (Diksi, 2021)
(Title: The Evaluation of Trump's Political Perspectives at The  "Save America Rally"). This paper explores Trump speech in online media CBC news entitled "Live Coverage: Protesters Swarm Capitol, Abruptly Halting Electoral Vote Count" in the point of view of discourse analysis. This research belongs to qualitative research. The method used to analyze is distributional and referential method. It analyzed Trump ideology's Perspectives through structure manifested by Emotive words, phrases, sentences from his speech, specifically it explored from critical discourse analysis conducted by Teun A .Van Dijk.  It resulted and indicated that Trump conveyed his political will by protesting the result of the ballots. He said there was fraud in the middle of the election. In fact, instead of protesting the election, he also conveyed the autocritics towards the government (himself). Key Words:  speech, Trumps, critical discourse analysis, ideology